Análise exergoeconômica de um sistema de trigeração de energia operando sob um Ciclo de Rankine Orgânico, acoplado a um Chiller de Absorção de Simples Efeito - Figueredo, Thiago de Souza (2019)
In this work, the energetic, exergetic and exergoecomic analysis are performed by the SPECO method, in a CCHP system. The system consists in a Organic Rankine Cycle (ORC), which operates with a Twin Screw expander, a Single Effect Absorption Chiller and a boiler. The heat source for the system considered is focused on the use of heat rejection inside an industrial facility, with temperatures below 100 ° C. A computational modeling was developed in the Engineering Equation Solver (EES) platform, which allows, through of the thermodynamic analysis, with the application of the concepts associated with the first and second law, the indicators and the exergetic costs of the flows. It is also implemented to the exergoeconomic assessments associated with each component. By exergetic analysis it is possible to calculate the thermal parameters of all flows, as well the energetic and exergetic efficiencies of the components of the system and how the irreversibilities must be applied to the processes. An exergoeconomic analysis can be made from a greater impact with an optimization of monetary costs. The application of the methodology by the method SPECO allows the quantification of costs and monetary for the waste, which can generate new inputs. Comparing the results of the energy efficiencies, it is possible to observe the behavior of the overall efficiency, with the degree of effectiveness of the components. The results obtained are analyzed in the form of graphs and tables.